2011
DOI: 10.1152/japplphysiol.01105.2010
|View full text |Cite
|
Sign up to set email alerts
|

Differential atrophy of the postero-lateral hip musculature during prolonged bedrest and the influence of exercise countermeasures

Abstract: As part of the 2nd Berlin BedRest Study (BBR2-2), we investigated the pattern of muscle atrophy of the postero-lateral hip and hamstring musculature during prolonged inactivity and the effectiveness of two exercise countermeasures. Twenty-four male subjects underwent 60 days of head-down tilt bedrest and were assigned to an inactive control (CTR), resistive vibration exercise (RVE), or resistive exercise alone (RE) group. Magnetic resonance imaging (MRI) of the hip and thigh was taken before, during, and at en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 50 publications
4
36
0
Order By: Relevance
“…In the context of deloading, the results are consistent with the relatively low degree and rate of GMed atrophy demonstrated in bed rest studies 8,25 and could imply that GMed is not necessarily adversely affected by a lack of gravitational stimulus.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the context of deloading, the results are consistent with the relatively low degree and rate of GMed atrophy demonstrated in bed rest studies 8,25 and could imply that GMed is not necessarily adversely affected by a lack of gravitational stimulus.…”
Section: Discussionsupporting
confidence: 80%
“…7 These local stabilising properties suggest that GMin may be more vulnerable than gluteus medius (GMed) to adverse changes in size or function in response to a lack of gravitational load, 8 as in swimming. Dysfunction of GMin may affect the ability to bear weight during functional tasks such as walking.…”
Section: Introductionmentioning
confidence: 99%
“…Countermeasure studies have been conducted during bed rest (e.g. Belavy et al, 2010;Blottner et al 2006;Miokovic et al, 2011), which provides an analogue of microgravity; a useful tool given the methodological constraints of conducting studies inflight (see below regarding methodological challenges). Members of the Reconditioning Topical…”
Section: Exercise-based Countermeasures To Minimise Effects Of Microgmentioning
confidence: 99%
“…With reference to biomechanical modelling (Torry et al, 2006) and radiological literature (Miokovic et al, 2011), the authors identified that these muscles have favorable morphological features to contribute to stability of the hip joint, much like the rotator cuff of the shoulder. It is for this reason that targeted interventions for improving deep hip external rotator strength are becoming a fundamental component of contemporary hip rehabilitation protocols (Bennell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It is for this reason that targeted interventions for improving deep hip external rotator strength are becoming a fundamental component of contemporary hip rehabilitation protocols (Bennell et al, 2014). Quadratus femoris (QF) is considered a particularly important constituent of the deep external rotators (Miokovic et al, 2011), yet due to the technical difficulty and perceived discomfort associated with accessing this deep muscle with fine wire electrodes, and the proximity to the sciatic nerve, it is only recently that a published account of QF EMG has been documented (Hodges et al, 2014). The investigation by Hodges et al on ten healthy participants confirmed that QF was highly active in maximum isometric hip external rotation and extension.…”
Section: Introductionmentioning
confidence: 99%